-3(k+1)-(7+4k)=-8k

Simple and best practice solution for -3(k+1)-(7+4k)=-8k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(k+1)-(7+4k)=-8k equation:



-3(k+1)-(7+4k)=-8k
We move all terms to the left:
-3(k+1)-(7+4k)-(-8k)=0
We add all the numbers together, and all the variables
-3(k+1)-(4k+7)-(-8k)=0
We multiply parentheses
-3k-(4k+7)-(-8k)-3=0
We get rid of parentheses
-3k-4k+8k-7-3=0
We add all the numbers together, and all the variables
k-10=0
We move all terms containing k to the left, all other terms to the right
k=10

See similar equations:

| 17b+4.75/5(b-2)=9.6 | | 0=-16t^2+1048t | | 3x2+23x=0 | | 7x-1=+5 | | -x2+4=200 | | 5r+20-r-3=5 | | 3/4x+16=1/8x+2 | | 18/g-11=9(-2+1/g)+8 | | 7(c+1)=6+6c | | (-1/6d=-4 | | 2×-5=4x-1 | | x+(3x-5)=75 | | 7y-3=5-3y | | 5-x/3=30 | | x+x+(x/6)+(x/6)=1 | | x+28=-58 | | 2k^2=10 | | 4k-40=-14k+14 | | 5x+1-x=7+3x-1 | | 3-y/2+2y=71 | | 518+49x=784+101x | | 5x+2=3x= | | x^2=16+(x-4/x+4) | | 5x-3(x-4)=-9+5x+12 | | 4(5x+2)=20 | | -n-23=5-3n | | 31=5-6x+8-x | | (2x+6)=(9x-4) | | s/4=21 | | -n-5=10-4n | | 8x-2=12/x | | 8x+1=5+4x |

Equations solver categories